La maîtrise du temps comme enjeu de lutte - Marie-Christine Bureau; Antonella Corsani (Temporalités)
The reform of the system of unemployment insurance for art and entertainment workers in France has created a long and intense social conflict. Here we defend the thesis that time control is a major stake in this conflict. The confrontation on the economic field (of employment and cultural industry) is coupled with another confrontation regarding time : the question of time is not limited to a regulation of working hours, it is intertwined with the « forms of life » to which every people aspires. These two coexist but the second is hardly perceived. This article aims at uncovering this aspect and exploring its significance.sociology, France, art and entertainment workers, working hours, acceleration, uncertainty, time control